2017
DOI: 10.1159/000447184
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Detection of Occult Thyroid Carcinoma with 11C-Choline PET/CT for High Risk Prostate Cancer

Abstract: We report a case of a 65-year-old male patient with high-risk prostate cancer, re-staged with 11C-choline positron emission tomography/computed tomography (PET/CT) for prostate specific antigen recurrences 3 years after radical prostatectomy and adjuvant radiation therapy. In addition to 2 suspicious presacral lymph nodes which were resected and proven to be metastatic, PET/CT revealed a very high uptake in a calcified thyroid nodule. Evaluation with fine needle aspiration was suspicious for thyroid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…However, a retrospective study of 368 patients focusing exclusively on abnormal F-choline uptake in the thyroid gland at PET/CT found two cases of thyroid carcinoma out of nine cases of atypical thyroid uptake (32). Case reports also demonstrated that focal uptake of F-choline in the thyroid should raise suspicion for malignancy (33)(34)(35). Thus, in agreement with the conclusion of a recent literature review evaluating the prevalence and clinical significance of focal incidental radiolabeled choline uptake in the thyroid gland (36), any abnormal thyroid uptake at F-choline PET/CT should be explored with at least a TSH and calcitonin assay and an ultrasonography.…”
Section: Discussionmentioning
confidence: 99%
“…However, a retrospective study of 368 patients focusing exclusively on abnormal F-choline uptake in the thyroid gland at PET/CT found two cases of thyroid carcinoma out of nine cases of atypical thyroid uptake (32). Case reports also demonstrated that focal uptake of F-choline in the thyroid should raise suspicion for malignancy (33)(34)(35). Thus, in agreement with the conclusion of a recent literature review evaluating the prevalence and clinical significance of focal incidental radiolabeled choline uptake in the thyroid gland (36), any abnormal thyroid uptake at F-choline PET/CT should be explored with at least a TSH and calcitonin assay and an ultrasonography.…”
Section: Discussionmentioning
confidence: 99%